Investigation of the contribution of vascular endothelial growth factor and its splicing axis to joint inflammation and damage in arthritis - Sohail, Roheena (2024)
Vascular Endothelial Growth Factor-A (VEGF-A) is a key regulator for endothelial cell function, promoting vascular permeability, growth, and angiogenesis. There is an increase in synovial angiogenesis and upregulation of angiogenic growth factors such as VEGF-A during articular joint inflammation in inflammatory arthritis (IA), such as rheumatoid arthritis (RA). This is a major contributor to disease progression.